Body image and self-perception in women with navel piercings. - Christine Coleman; Helge Gillmeister (PLoS ONE, 2022)
The present study investigated how women's body image and body-perceptual processes are affected by navel piercings, an embellishment of the abdominal region women often feel negatively about. We probed perceptual (response times), cognitive (surveys), affective (aesthetic ratings) and neural (event-related potentials, ERPs) facets of (own) body perception. We found that navel piercings are primarily motivated by the desire to enhance one's body image, and can significantly improve bodily self-perception relative to before and to imagined removal of the piercing. Hence, body image concerns in women with navel piercings were found to be comparable to those of a control group; and their aesthetic ratings of other women's abdomens only differed, positively, for images depicting navel piercings. ERPs indicated that the sight of navel piercings enhances early structural encoding of bodies as well as late emotional-motivational processes, especially in women with navel piercings. We further found a strong self-advantage in both cortical and behavioural responses during recognition of own and others' abdomens, especially for images displaying the piercing. Altogether, findings suggest that navel piercings become strongly, and beneficially, integrated into women's bodily self image. Such piercings may thus be seen as expressions of body care that can protect against self-harming thoughts and behaviours.